Monitoring of rolling bearing with inner race fault using parameters of vibration birhythmic stochastic recurrence (Моделювання, керування та інформаційні технології, 2025)
An analysis of the covariance and spectral structure of the Hilbert transform of biperiodically non-stationary random processes, which are a model of signals with double rhythmicity, are provided. The obtained relations for the cross-covariance and cross-spectral characteristics of the signal and its Hilbert transform.Наведено аналіз кореляційної та спектральної структури перетворення Гільберта біперіодично нестаціонарних випадкових процесів, які є моделлю сигналів із подвійною ритмічністю. Отримано співвідношення для взаємокореляційних та взаємоспектральних характеристик сигналу та його перетворення Гільберта.